THE IMPACT OF CREATIVE DRAMA EDUCATION ON SOCIAL AND MENTAL WELL-BEING LEVELS OF UNIVERSITY STUDENTS - Ayşegül ARSLAN (Fırat University, 2019)
In this study, it was aimed to investigate the effects of creative drama on social intelligence and mental well-being in university students. In this study participated 12 third class students (experimental group) who selected "Drama" as an elective course and 11 third grade students (control group) who did not take drama courses from Necmettin Erbakan University, Faculty of Tourism, Department of Recreation Management in 2017-18 academic year. This study is a Pretest – Posttest Nonequivalent Groups Quasi – Experiment design. As data collection tools were used Tromso Social Intelligence Scale and Mental Goodness Scale in the study. In the analysis of the data, was used SPSS 21 package program. It was determined that the data showed normal distribution with Shapiro Wilk test. In the analysis of the collected quantitative data were used independent t-test and Paired Sample t Test from parametric analysis types. According to research findings; While it was observed that the experimental group had an increase in all subscales of social intelligence scale and averages in the level of mental well-being scale; it was found that there was a statistically significant difference between the experimental and control groups in the social skills subscale of the post test (p